Possible Traces of Citizen Comedy in "A Man da Santiña" by Ramón Cabanillas - Fernández Poza, Óscar (Madrygal. Revista de Estudios Gallegos, 2015)
This research aims to find possible traces of citizen comedy in Ramón Cabanillas’ play A Man da Santiña. First, we shall see how Galician dramaturgy has changed over the course of time. Then, we shall define the genre based on existing premises in Catalonian drama. Finally, we shall conclude with an analysis of the aforementioned play.
Keywords: Galician drama; Catalonian references; Ramón Cabanillas; A man da Santiña; citizen comedy